Stability-based damage assessment and rapid post-disaster quantification of a latticed shell subjected to earthquake loading. (1st March 2020) - Li, Y.G.; Hong, H.P.
Highlights: Developed damage factor and fragility curve based on critical load factors. Investigated effect of unidirectional versus bidirectional ground motions on the fragility curve. Provided a simple probabilistic procedure to estimate the remaining critical load factor for global stability. Developed a post-earthquake rapid screening chart to assess spherical latticed shell. Abstract: Damage of latticed shells due to the earthquake has been observed and the damage can affect the critical load for global instability. In the present study, an investigation of the critical load factor of a spherical latticed dome after sustaining seismic excitation is carried out. The evaluation of the damage factor is presented based on the initial and remaining critical load factors for global instability before and after the structure sustained an earthquake. The statistics and the probabilistic model of the damage factor of the latticed shell are presented by considering the record-to-record variability and the use of the uni- and bi-directional seismic excitation. The results show the importance of considering bidirectional ground motions to assess the damage factor. Fragility curves are estimated and are used as a basis to develop an approach for practical and rapid post-disaster quantification of a latticed shell for temporary emergency use. The qualification can be carried out using the observed ground motion record at the structural site. If the record of the sustained seismic event is unavailable, a practical chart for qualifying the structure for temporary emergency use is recommended based on the magnitude and epicentral distance of the seismic event.